Effects of super-dosing phytase in diets with adequate phosphorus on finishing pig growth performance and carcass characteristics - Kari Beth Langbein; Jason C Woodworth; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz; Joel M DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 274 finishing pigs (PIC 1050 × 327, initially 129 lb) were used in a 78-d study to compare the effects of adding high levels of three different sources of phytase (super-dosing) on growth performance and carcass characteristics of finishing pigs. Pigs were randomly allotted to pens with 7 or 8 pigs per pen and 9 replications per treatment. Dietary treatments included a corn-soybean meal—based control diet that was formulated to meet the available P requirements of the pigs without any added phytase, or three diets that were formed by adding 2,000 FTU/kg of phytase from 1 of 3 different phytase sources to the basal diet. The three phytase sources were Quantum Blue 5 G (AB Vista, Chesterfield, MO), Ronozyme HiPhos (GT) 2500 (DSM Nutritional Products, Parsippany, NJ), or Optiphos 1000 (Enzyvia, Sheraton, IN). Overall, regardless of source, super-dosing phytase had no effect (P>0.26) on ADG, ADFI, or F/G; furthermore, there were no effects (P>0.36) on any of the carcass criteria measured. In conclusion, in this environment with nutritionally adequate diets, this study suggests that super-dosing phytase had no beneficial effects on finishing pig growth or carcass performance.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Phosphorous; Phytase; Finishing pig